Programmable multistage small-molecule nano-photosensitizer for multimodal imaging-guided photothermal therapy. (February 2023) - Ma, Huihui; Mu, Xueluer; Tang, Ying; Li, Chunfeng; Wang, Yukun; Lu, Yingxi; Zhou, Xianfeng; Li, Zhibo
Abstract: Photothermal therapy has become a promising approach as precision medicine to allow spatial control of therapeutic effect only in the site of interest. However, the full potential of PTT has not been realized due to the lack of simple photosensitizers (PSs) that can overcome multistage biological barriers and improve theranostic efficiency. Here, we develop a small molecule-based PS to enhance tumor-specific PTT by programming multistage transport and activation properties in molecular architecture. This PS can self-assemble into stable nanoparticles that accumulate passively in tumor, and then actively internalize through ligand-mediated endocytosis. Subsequently, the programmable degradable linkers are selectively cleaved, enabling size shrinkage for better tumor penetration, binding albumin to enhance the near-infrared fluorescence for low-background imaging, and activating photothermal conversion for tumor suppression. The self-delivery process can be programmed, representing the first multistage small-molecule nano-photosensitizer that overcomes multiple biological barriers and improves the PTT index of tumor. Statement of Significance: Photothermal therapy has become a promising approach as precision medicine, but has not been realized due to the lack of simple photosensitizers that can overcome multistage biological barriers and improve theranostic efficiency. In this contribution, we solve this dilemma by developing a small molecule-based photosensitizer by programming multistage transport and activation properties in molecular architecture, which could self-assemble into stable nanoparticles that accumulate passively in tumor, and actively internalized through ligand-mediated endocytosis. Subsequently, the programmable activation by ROS triggered size reduction for tumor penetration and minimized the phototoxicity to normal tissue. The activatable fluorescence and photothermal properties made the photosensitizer intrinsically suitable for multimodal imaging-guided PTT, providing a promising supramolecular nanomedicine towards tumor precise diagnosis and therapy. Graphical abstract: Image, graphical abstract